Kompetensi Komunikasi Politik Politisi Perempuan Jawa Timur (Faculty of Communications Science, Dr. Soetomo University, 2018)
As politicians, women have the ability to politicize well. Some local leaders held by women are able to perform well in developing the region. Some women politicians are able to have a strategic role as chairman or deputy chairman of the commission although there are not many. It's just that their activities and actions are never exposed in the media. With the exposure of women politicians in constituent media and the public knows who and how they are so when performing political functions will be easier than when they are not known to anyone. In this research, the competence of interpersonal communication in women politicians is weak. Women politicians are very weak in the mastery of knowledge about politics so that the process of adaptation is not good. The leadership factor currently held by women politicians contributes in building the communication competence of women politicians, although not large. The contribution is more evident when women politicians become the number one in an area. The leadership factor currently held by women politicians contributes in building the communication competence of women politicians, although not large. The contribution is more evident when women politicians become the number one in an area Keywords: female politicians, political communication competence